Contextualisation of Zhihar with Shari’ah Maqasid Approach - Hasyim, Muh. Fathoni; Masruhan; Nur Lailatul Musyafa’ah; Abd Basit (Technium Social Sciences Journal, 2024)
Zhihar, a form of divorce from pre-Islamic Arab society, was abolished during the Islamic period through the Qur’an and the sunnah of the prophet. This article undertakes a re-examination of zhihar in a modern context, with a particular focus on the maqasid Shari’ah approach. This approach, which underscores the fundamental objectives of Islamic law, including the safeguarding of religion, soul, intellect, heredity, property, and self-esteem, plays a crucial role in reinterpreting the concept of zhihar to serve the benefit of the ummah in the contemporary era. By conducting a textual and contextual study of the Qur’an, the sunnah of the Prophet, and the opinions of scholars, this article concludes that zhihar in the modern context should be viewed as a means of protecting family honor and preserving the harmony of the marital relationship. The study utilizes a descriptive-analytical method, guided by the maqasid Shari’ah approach, to assess the relevance and application of zhihar in the context of Muslim life today, thereby providing a comprehensive understanding of the topic